2003
DOI: 10.1042/bj20030414
|View full text |Cite
|
Sign up to set email alerts
|

Protein S-thiolation targets glycolysis and protein synthesis in response to oxidative stress in the yeast Saccharomyces cerevisiae

Abstract: The irreversible oxidation of cysteine residues can be prevented by protein S-thiolation, a process by which protein SH groups form mixed disulphides with low-molecular-mass thiols such as glutathione. We report here the target proteins which are modified in yeast cells in response to H(2)O(2). In particular, a range of glycolytic and related enzymes (Tdh3, Eno2, Adh1, Tpi1, Ald6 and Fba1), as well as translation factors (Tef2, Tef5, Nip1 and Rps5) are identified. The oxidative stress conditions used to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
244
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 288 publications
(260 citation statements)
references
References 41 publications
14
244
2
Order By: Relevance
“…In the latter mutant, Tpi1p and Adh1p were highly oxidized, consistent with our observations of disulfide bonds in isoforms of these enzymes in the Δidp2Δzwf1 mutant strain. There are also some interesting correlations between results of these proteomic screens for cysteine oxidation [55, current study] with those obtained by Shenton and Grant [17] who examined yeast proteins that were S-thiolated, i.e., that formed mixed disulfide bonds with compounds like glutathione, in response to an acute challenge with hydrogen peroxide. Commonly labeled proteins included the glycolytic enzymes Tpi1p, Tdh3p, Eno2p, and Adh1p.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…In the latter mutant, Tpi1p and Adh1p were highly oxidized, consistent with our observations of disulfide bonds in isoforms of these enzymes in the Δidp2Δzwf1 mutant strain. There are also some interesting correlations between results of these proteomic screens for cysteine oxidation [55, current study] with those obtained by Shenton and Grant [17] who examined yeast proteins that were S-thiolated, i.e., that formed mixed disulfide bonds with compounds like glutathione, in response to an acute challenge with hydrogen peroxide. Commonly labeled proteins included the glycolytic enzymes Tpi1p, Tdh3p, Eno2p, and Adh1p.…”
Section: Discussionmentioning
confidence: 56%
“…A protein translation factor, Tef2p, which demonstrated disulfide bond content in some of our cellular extracts, was also identified as an S-thiolated protein. Shenton and Grant [17] found that S-thiolation correlated with a reduction in activities of several glycolytic enzymes and in rates of protein synthesis. These effects could be reversed by removal of hydrogen peroxide, suggesting that S-thiolation functions to redirect metabolic flux through the pentose phosphate pathway to increase production of NADPH during transient exogenous oxidative challenge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations